Konstrukcije iz lesa na svetovnih razstavah - Slivnik, Lara (Les (Ljubljana), 2010)
The paper presents twelve of the most interesting structures that were constructed at world expositions. They were all made of timber or timber-based materials. The architectural design timber structure of these pavilions are described. Structural system made of timber is very appropriate for the engineered structures made of prefabricated items. At the end the paper presents the future possible results in structure, architectural design, and construction made of timber.
Keywords: javne zgradbe; lesene konstrukcije; paviljoni; zgodovinski pregledi